2019
DOI: 10.1007/s00404-019-05215-8
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed umbilical cord clamping on maternal and neonatal outcomes

Abstract: Purpose Policies for timing of cord clamping varied from early cord clamping (ECC) in the first 30 s after birth, to delayed cord clamping (DCC) in more than 30 s after birth or when cord pulsation has ceased. DCC, an inexpensive method allowed physiological placental transfusion. The aim of this article is to review the benefits and the potential harms of early versus delayed cord clamping. Methods Narrative overview, synthesizing the findings of the literature retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 77 publications
(239 reference statements)
2
62
0
8
Order By: Relevance
“…(2019) found bene ts involving higher Hemoglobin levels and reduced anemia. Also, higher levels of iron supplies have been found in infants up to 6 months (20). Another study from 2019 found higher levels of Oxygen in babies with delayed cord clamping than in those who had early cord clamping, in addition to slower heart beat and higher Apgar scores (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2019) found bene ts involving higher Hemoglobin levels and reduced anemia. Also, higher levels of iron supplies have been found in infants up to 6 months (20). Another study from 2019 found higher levels of Oxygen in babies with delayed cord clamping than in those who had early cord clamping, in addition to slower heart beat and higher Apgar scores (12).…”
Section: Discussionmentioning
confidence: 99%
“…Another study from 2019 found higher levels of Oxygen in babies with delayed cord clamping than in those who had early cord clamping, in addition to slower heart beat and higher Apgar scores (12). Studies have not found an elevated risk of postpartum haemorrhage of the mothers, and the bene ts to the baby is equally high or higher when delivered by Caesarean section (11,12,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Pain studies have described a clinically significant reduction in pain as a reduction of 1.3–2.0 cm on a 10 cm VAS (Jensen, Chen, & Brugger, 2003; Rowbotham, 2001; Todd, Funk, Funk, & Bonacci, 1996), and 15 mm is the minimum effect value (Conti et al., 2019). The standard deviation for episiotomy suture pain in the literature was 18–26 mm (Qian et al., 2019). To detect at least a 15 mm mean difference in the VAS with 90% power and a significance level of 0.05, a total of 240 participants was required, approximately 60 per group.…”
Section: Methodsmentioning
confidence: 99%
“…Delayed umbilical cord clamping means that the umbilical cord is clamped 30 to 90 s after delivery or after the umbilical cord pulsation disappears spontaneously (Mohammad, Tailakh, Fram, & Creedy, 2019; Qian, Ying, Wang, Lu, & Hua, 2019); at present, this line of research is also the focus of clinical attention. The umbilical cord is the channel for nutrient metabolism and material exchange between foetus and mother.…”
Section: Introductionmentioning
confidence: 99%
“…This practice allows the transfer of 25-35 mL/kg of placental blood to the newborn, thus increasing iron stores by approximately 30% after three minutes of DCC [26]. Indeed, DCC, compared to immediate cord clamping, is associated with higher hemoglobin concentration in first weeks after birth in both term and preterm newborns, and lower rates of RBC transfusions in preterm newborns [75][76][77]. In the long term, DCC maintains its benefits, as evidenced by the higher ferritin levels and the lower incidence of ID at six months of age in term neonates [2,75,78].…”
Section: Preventionmentioning
confidence: 99%